2005
DOI: 10.1136/qshc.2004.011148
|View full text |Cite
|
Sign up to set email alerts
|

Improving medical emergency team (MET) performance using a novel curriculum and a computerized human patient simulator

Abstract: Problem: Advance cardiac life support (ACLS) training does not address coordination of team resources to improve the ability of teams to deliver needed treatments reliably and rapidly. Our objective was to use a human simulation training educational environment to develop multidisciplinary team skills and improve medical emergency team (MET) performance. We report findings of a crisis team training course that is focused on organization. Setting: Large center for human simulation training at a university affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
129
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(133 citation statements)
references
References 16 publications
0
129
1
3
Order By: Relevance
“…According to Ten Eyck et al (2010), tasks were selected based on the criteria that they were "clear and measurable" (p. 141). It was suggested that task completion is an objective measure (DeVita et al, 2005) and "less susceptible to inter-rater differences" (p. 330). Lavigne Fadale et al (2014) reported 100% interrater reliability.…”
Section: Assessment Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ten Eyck et al (2010), tasks were selected based on the criteria that they were "clear and measurable" (p. 141). It was suggested that task completion is an objective measure (DeVita et al, 2005) and "less susceptible to inter-rater differences" (p. 330). Lavigne Fadale et al (2014) reported 100% interrater reliability.…”
Section: Assessment Measuresmentioning
confidence: 99%
“…As noted above, all of the studies reviewed included simulation-based learning using a high-fidelity simulator. Thirteen studies compared pre-test and post-test results following an HFS learning program (Buckley & Gordon, 2011;Dadiz et al, 2013;DeVita et al, 2005;Gilfoyle et al, 2007;Huseman, 2012;Jankouskas et al, 2007;Liaw et al, 2011;Przybyl et al, 2015;Schubert, 2012;Shinnick & Woo, 2013;Sittner et al, 2009;Straka et al, 2012;Wolf, 2008). Standard education was compared to standard education plus HFS learning in four studies (Hall, 2015;Jankouskas et al, 2011;Maneval et al, 2012;Singer et al, 2013).…”
Section: Overview Of Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical experience alone has not been associated with improved team performance [5]; therefore, training programs are focusing on team dynamics during medical crises as a point of improvement. Since team dynamics can be taught and practiced in simulated environments [6,7], various types of simulation have been developed – computer-based, manikin, and standardized patient [2,3,8]. These training tools may not be available in many hospitals and training facilities in low-middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Since interprofessional teamwork has been linked with patient outcomes [1] and team dynamics can be improved with simulation [6,7], we set out to determine if team dynamics can be improved via remote simulation in resource-limited areas. The original purpose of the simulations was to assess the effectiveness of CERTAIN-ELITE training; however, we wanted to utilize this pre-existing platform to assess the effects of remote simulation on team dynamics.…”
Section: Introductionmentioning
confidence: 99%